Research-grade scoring for the functional movement screen and relationships with athletic performance tests in team sport athletes - Lockie, R. G.; Jalilvand, F.; Jordan, C. A.; Callaghan, S. J.; Jeffriess, M. D.; Luczo, T. M.; Schultz, A. B. (The Journal of Performance Enhancement, 2015)
There are limitations in using the traditional Functional Movement Screen (FMS) to identify deficiencies affecting athletic performance. Despite this, no research has analyzed the research-grade FMS scoring system with regards to athletic performance, where screens are weighted to increase their sensitivity. This research investigated relationships between the research-grade FMS and selected screens, with multidirectional speed and jump tests typically used to assess team sport athletes.